Performance Grading and Constraints Analysis of Farmer Producer Organisations (FPOs) in Anantapuramu District of Andhra Pradesh - Ravikishore, M.; Royal, A. Prudvi; Gopal, P. V. Satya; Johnson, M.; Rani, Seedari Ujwala; Reddy, B. K. Kishore; Sujathamma, P.; Rani, K. Sudha; Supriya, P. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the period from September, 2020 to August, 2022 in the Anantapuram district of Andhra Pradesh, India to evaluate the functional performance and constraints faced by Farmer-producer Organizations (FPOs). Farmer Producer Organization (FPO) is believed to improve the livelihood of farmers by collectivizing them for input purchase and providing forward and backward linkages. Performance Grading Tool for FPOs developed by the National Bank for Agriculture and Rural Development (NABARD) was used for measuring the performance of each FPO and the Garret ranking method was used for constraint analysis. Purposive cum simple random sampling was followed where from each FPO, five Board of Directors (BOD) and fifteen farmer members were selected randomly and thus, comprising a total sample size of 100 respondents from Five FPOs. The findings of the study revealed that Tadipatri Horticulture FPO was categorized under ‘Grade-A’ FPO, and three FPOs viz. Sri Venkateswara Swamy FPO, Sri Ramaswamy FPO, and Sri Peddamma Thalli FPO were categorized under ‘Grade B’, and one FPO namely, Narpala Rythunestam FPC Ltd was categorized under Grade-C. With respect to constraint analysis, obtaining the remunerative price in local markets was the major constraint followed by fluctuation in market prices. It was concluded that FPOs should have market awareness and market linkages with corporate buyers/processors or any other agencies for fetching better returns and to overcome the constraints.